A low-smoke, halogen-free, flame-retardant polyolefin sheathed power cable
By using outer sheath composite material, the problems of insufficient high-temperature resistance and poor flame retardant performance in high-temperature environments are solved, and the efficient flame retardant and high-temperature resistance of power cable sheath are improved, reducing fire risk .
Patent Information
- Application Number
- CN202410865005.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-07-01
- Publication Date
- 2025-02-11
- Estimated Expiration
- 2044-07-01
AI Technical Summary
When used in high-temperature environments, polyethylene materials have insufficient high-temperature resistance, which can easily lead to softening, deformation and even melting of the sheath, increasing the risk of short circuits and fires, and at the same time, its flame retardant performance is not good.
It adopts outer sheath composite materials, including metallocene linear low-density polyethylene, ethylene-vinyl acetate copolymer, high-density polyethylene, flame retardant additives, high-temperature resistant components, antioxidants, crosslinking agents and lubricants. Through high-speed kneading and twin screw extrusion mechanisms, an outer sheath with excellent mechanical properties and flame retardant properties is formed.
It improves the high temperature resistance and flame retardant properties of polyethylene materials, reduces the softening and fire risk of power cable sheath in high temperature environments, and effectively prevents the spread of fire and ensures safety.
Smart Images

Figure CN118652489B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of power cable manufacturing, and in particular to a low-smoke, halogen-free, flame-retardant polyolefin sheathed power cable. Background Art
[0002] With the development and progress of science and technology, the demand for electricity in society is also increasing. As a product for transmitting and distributing electric energy, power cables transport electricity for commercial, industrial and residential areas, distribute electricity to electrical equipment, and meet the electricity needs of users. The sheath of power cable plays an important role in ensuring the normal operation of cables, protecting cables and extending the service life of cables; the sheath of power cable can be made of polyvinyl chloride, polyethylene, polyurethane, vinyl acrylate copolymer, fluoroplastics, rubber and other materials. Polyethylene material has excellent chemical stability, good resistance to corrosive substances such as acids and alkalis, is not easy to be corroded, has excellent low temperature resistance, can maintain good performance at low temperatures, has excellent electrical insulation, greatly improves safety, has light weight, is easy to transport, and is convenient for repair, construction and maintenance. It has good economic benefits, low price, odorless and non-toxic, environmentally friendly, and does not produce hydrogen halide gas and smoke when burned. Therefore, polyethylene can be used as a preparation material for power cable sheath.
[0003] However, polyethylene as a material for preparing power cable sheaths still has some shortcomings in performance. For example, the high temperature resistance of polyethylene materials is insufficient. During the use of power cables, heat is generated due to the current and external influences. Long-term high temperature environment will cause the sheath to soften, deform or even melt, and the conductor in the cable will be exposed, which can easily cause a short circuit and fire, posing a great impact on safety. In addition, the flame retardancy of power cable sheaths is an important performance to ensure cable safety. It can slow down the spread of fire and reduce the damage and loss caused by fire to personnel and equipment. However, the flame retardancy of polyethylene materials is not good. Therefore, it is necessary to improve polyethylene materials to meet the use requirements of power cable sheaths in different environments.
[0004] The patent with application number CN202211095704.2 discloses a low-smoke halogen-free flame-retardant power cable. The outer sheath of the invention includes the following components: high-density polyethylene, poly-1-butene, silane-modified ethylene-vinyl acetate copolymer, polyethylene grafted maleic anhydride, flame retardant, nano calcium carbonate, methyl propylene-cage polysilsesquioxane coated intercalated montmorillonite, dibenzoyl peroxide, anisil; the prepared power cable outer sheath material has excellent mechanical properties and flame retardant properties, which can effectively protect the cable core from mechanical damage and prevent the spread of fire in the event of a fire, avoiding greater losses. It does not contain bromine elements and meets the requirements of low smoke and flame retardancy. However, the invention does not take into account the high temperature resistance required for power cables to work in high temperature environments in actual applications. Therefore, the present invention provides a low-smoke halogen-free flame-retardant polyolefin sheathed power cable that can work stably in high temperature environments, which is of great significance for safety. Summary of the invention
[0005] The purpose of the present invention is to provide a low-smoke, halogen-free, flame-retardant polyolefin sheathed power cable, which solves the following technical problems:
[0006] (1) Solved the problem of poor flame retardancy of polyethylene materials;
[0007] (2) The problem of poor high temperature resistance of polyethylene materials has been solved.
[0008] The purpose of the present invention can be achieved through the following technical solutions:
[0009] A low-smoke, halogen-free, flame-retardant polyolefin sheathed power cable, wherein the manufacturing method of the power cable comprises the following steps:
[0010] (1) Twisting copper wires to form a copper core, coating the outer surface of the copper core with a polyethylene insulation layer through an extrusion device, and sheathing the outer surface of the copper core coated with the insulation layer with a copper wire braided shielding layer to obtain a cable core;
[0011] (2) Wrapping the outer surface of the cable core with a single-sided corrugated aluminum strip to form an inner protective layer, filling the inner protective layer with an alkali-free rock wool rope to form a filling layer, coating the outer surface of the filling layer with an armor layer made of twisted steel wires, and extruding and coating the outer sheath composite material on the surface of the armor layer to obtain a power cable;
[0012] The outer sheath composite material comprises the following raw materials in parts by weight: 50-60 parts of metallocene linear low-density polyethylene, 10-20 parts of ethylene-vinyl acetate copolymer, 5-15 parts of high-density polyethylene, 3-6 parts of flame retardant additives, 4-8 parts of high-temperature resistant components, 1-3 parts of antioxidants, 1.5-3.5 parts of cross-linking agents, and 0.3-0.5 parts of lubricants.
[0013] Furthermore, the preparation method of the outer sheath composite material comprises the following steps:
[0014] Step 1: Add metallocene linear low-density polyethylene, ethylene-vinyl acetate copolymer, high-density polyethylene, flame retardant additives, high-temperature resistant components, antioxidants, crosslinking agents, and lubricants into a high-speed kneading machine, set the temperature to 100-120°C, knead for 30-60 minutes, and then cool to room temperature to obtain an outer sheath mixture;
[0015] Step 2: Add the outer sheath mixture into a twin-screw extruder, set the temperature to 160-180° C., set the screw speed to 150-300 r / min, melt-extrude and granulate to obtain an outer sheath composite material.
[0016] Furthermore, the antioxidant is antioxidant 1010 or antioxidant 1076; the cross-linking agent is diisopropyl peroxide or dibenzoyl peroxide; and the lubricant is any one of magnesium stearate, stearic acid, and polyethylene wax.
[0017] Furthermore, the method for preparing the flame retardant additive comprises the following steps:
[0018] Step A, adding boehmite and glycine to deionized water, ultrasonically dispersing for 15-30 minutes, reflux reaction, centrifuging, washing, and drying at 55-65° C. for 6-8 hours to obtain modified boehmite;
[0019] Step B, adding the modified boehmite to tetrahydrofuran, ultrasonically dispersing for 10-15 minutes, adding diethyl allyl phosphate and triethylamine, stirring and reacting for 8-10 hours, filtering, washing and drying to obtain a flame retardant additive.
[0020] By adopting the above technical scheme, the active hydroxyl groups on the surface of boehmite can undergo an esterification reaction with the carboxyl groups in the glycine structure to obtain modified boehmite with amino groups. Through the catalytic action of triethylamine, the amino groups in the modified boehmite and the unsaturated olefins in the diethyl allyl phosphate structure undergo an addition reaction to obtain a flame retardant additive.
[0021] Furthermore, in step A, the average particle size of the boehmite is 3.5 μm.
[0022] Furthermore, in step A, the reflux reaction time is 14-18 hours.
[0023] Furthermore, the preparation method of the high temperature resistant component is as follows:
[0024] Add the carboxyl-terminated polybutadiene liquid rubber to N,N-dimethylformamide, stir and dissolve, then add 2-(4-aminophenyl)-5-aminobenzimidazole and a catalyst, react at room temperature for 8-12 hours, and obtain a high temperature resistant component after reduced pressure distillation and drying.
[0025] By adopting the above technical scheme, under the action of a catalyst, the active carboxyl groups in the carboxyl-terminated polybutadiene liquid rubber structure and the amino groups in the 2-(4-aminophenyl)-5-aminobenzimidazole structure undergo continuous amidation reactions to obtain a high temperature resistant component.
[0026] Furthermore, the number average molecular weight of the carboxyl-terminated polybutadiene liquid rubber is 1,000.
[0027] Furthermore, the catalyst is 4-dimethylaminopyridine and N,N-dicyclohexylcarbodiimide.
[0028] Beneficial effects of the present invention:
[0029] (1) The flame retardant additive prepared by the present invention improves the compatibility between boehmite and the polyethylene matrix by organically modifying boehmite. The boehmite can be evenly dispersed in the polyethylene matrix material to avoid the agglomeration problem. Therefore, the advantages of boehmite can be effectively exerted to enhance the mechanical properties such as tensile strength in the polyethylene material. At the same time, boehmite can play a synergistic flame retardant role with the nitrogen-phosphorus flame retardant system. The combination of boehmite and the nitrogen-phosphorus flame retardant system also reduces the precipitation of small molecular phosphate flame retardants, giving the polyethylene material flame retardant properties, which can effectively prevent the spread of fire, protect life and property safety, and reduce losses.
[0030] (2) The high temperature resistant component prepared by the present invention has a benzimidazole type high rigidity structure, which can be introduced into the polyethylene matrix to improve the high temperature resistance of the polyethylene matrix. In addition, when subjected to external force impact, the molecular chain of polybutadiene can be used for buffering, absorbing and dispersing stress, thereby improving the toughness of the polyethylene matrix. At the same time, the high temperature resistant component can be cross-linked with the polyethylene matrix under the action of the cross-linking agent to form a more stable network structure, which can further improve the high temperature resistance and toughness of the polyethylene matrix, reduce the risk of softening, deformation and cracking of the power cable sheath, and reduce the occurrence of fire accidents.
[0031] Of course, any product implementing the present invention does not necessarily need to achieve all of the advantages described above at the same time. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the accompanying drawings required for describing the embodiments will be briefly introduced below. Obviously, the accompanying drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other accompanying drawings can be obtained based on these accompanying drawings without paying creative work.
[0033] Figure 1 This is an infrared spectrum of the flame retardant additive prepared in the example;
[0034] Figure 2 It is the infrared spectrum of the high temperature resistant component prepared in the embodiment. DETAILED DESCRIPTION
[0035] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0036] Example 1
[0037] 1. Preparation method of flame retardant additives
[0038] Step A, adding 3.2 g of boehmite with an average particle size of 3.5 μm and 2.8 g of glycine into deionized water, ultrasonically dispersing for 25 min, reflux reacting for 18 h, centrifuging, washing, and drying at 60° C. for 6 h to obtain modified boehmite;
[0039] Step B: add 3 g of modified boehmite to tetrahydrofuran, ultrasonically disperse for 10 min, add 2.5 g of diethyl allyl phosphate and 0.5 g of triethylamine, stir and react for 9 h, filter, wash and dry to obtain a flame retardant additive.
[0040] The sample was prepared by potassium bromide tableting method, and the flame retardant additive was tested by infrared spectrometer using Fourier transform infrared spectrometer. Figure 1 As shown, the spectral wavenumber test range is 4000cm -1 -500cm -1 , analysis shows that in the infrared spectrum of flame retardant additives, 3411cm -1 The absorption peak of NH in the imine group appeared at 1720 cm -1 The absorption peak of C=O in the ester group appeared at 1221cm -1 The P=O absorption peak of the phosphate group appeared at 945 cm -1 The absorption peak of AI-OC appears at .
[0041] 2. Preparation method of high temperature resistant component
[0042] 3 g of terminal carboxyl polybutadiene liquid rubber with a number average molecular weight of 1000 was added to N,N-dimethylformamide, and after stirring to dissolve, 0.7 g of 2-(4-aminophenyl)-5-aminobenzimidazole, 0.2 g of 4-dimethylaminopyridine and 0.3 g of N,N-dicyclohexylcarbodiimide were added, and the mixture was reacted at room temperature for 10 hours. After reduced pressure distillation and drying, a high temperature resistant component was obtained.
[0043] The sample was prepared by potassium bromide tablet method, and the high temperature resistant components were tested by Fourier infrared spectrometer, such as Figure 2 As shown, the spectral wavenumber test range is 4000cm -1 -500cm -1 , analysis shows that in the infrared spectrum of the high temperature resistant component, 3413cm -1 The absorption peak of nitrogen-hydrogen bond in amide group appeared at 3350cm -1 The absorption peak of imidazole ring nitrogen hydrogen bond appeared at 3014 cm -1 The absorption peak of double carbon-hydrogen bond appeared at 1660 cm -1 The absorption peak of the carbon-oxygen double bond in the amide group appeared at 1294 cm -1 The absorption peak of carbon-nitrogen bond appears at
[0044] 3. Preparation method of outer sheath composite material
[0045] Step 1: Add 50g of metallocene linear low-density polyethylene, 10g of ethylene-vinyl acetate copolymer, 5g of high-density polyethylene, 3g of flame retardant additives, 4g of high-temperature resistant components, 1g of antioxidant 1010, 1.5g of diisophenyl peroxide, and 0.3g of polyethylene wax into a high-speed kneader, set the temperature to 100°C, knead for 30 minutes, and then cool to room temperature to obtain an outer sheath mixture;
[0046] Step 2: Add the outer sheath mixture into a twin-screw extruder, set the temperature to 160° C., set the screw speed to 150 r / min, melt-extrude and granulate to obtain an outer sheath composite material.
[0047] Example 2
[0048] Preparation method of outer sheath composite material
[0049] Step 1, add 55g of metallocene linear low-density polyethylene, 15g of ethylene-vinyl acetate copolymer, 10g of high-density polyethylene, 5g of the flame retardant additive prepared in Example 1, 6g of the high-temperature resistant component prepared in Example 1, 2g of antioxidant 1010, 2.5g of diisophenyl peroxide, and 0.4g of polyethylene wax into a high-speed kneader, set the temperature to 110°C, knead for 45min, and then cool to room temperature to obtain an outer sheath mixture;
[0050] Step 2: Add the outer sheath mixture into a twin-screw extruder, set the temperature to 170° C., set the screw speed to 250 r / min, melt-extrude and granulate to obtain an outer sheath composite material.
[0051] Example 3
[0052] Preparation method of outer sheath composite material
[0053] Step 1: add 60g of metallocene linear low-density polyethylene, 20g of ethylene-vinyl acetate copolymer, 15g of high-density polyethylene, 6g of the flame retardant additive prepared in Example 1, 8g of the high-temperature resistant component prepared in Example 1, 3g of antioxidant 1010, 3.5g of diisophenyl peroxide, and 0.5g of polyethylene wax into a high-speed kneader, set the temperature to 120°C, knead for 60min, and then cool to room temperature to obtain an outer sheath mixture;
[0054] Step 2: Add the outer sheath mixture into a twin-screw extruder, set the temperature to 180° C., set the screw speed to 300 r / min, melt-extrude and granulate to obtain an outer sheath composite material.
[0055] Comparative Example 1
[0056] Preparation method of outer sheath composite material
[0057] Step 1, add 55g of metallocene linear low-density polyethylene, 15g of ethylene-vinyl acetate copolymer, 10g of high-density polyethylene, 5g of the flame retardant additive prepared in Example 1, 2g of antioxidant 1010, 2.5g of diisophenyl peroxide, and 0.4g of polyethylene wax into a high-speed kneader, set the temperature to 110°C, knead for 45 minutes, and then cool to room temperature to obtain an outer sheath mixture;
[0058] Step 2: Add the outer sheath mixture into a twin-screw extruder, set the temperature to 170° C., set the screw speed to 250 r / min, melt-extrude and granulate to obtain an outer sheath composite material.
[0059] Comparative Example 2
[0060] Preparation method of outer sheath composite material
[0061] Step 1, add 55g of metallocene linear low-density polyethylene, 15g of ethylene-vinyl acetate copolymer, 10g of high-density polyethylene, 6g of the high-temperature resistant component prepared in Example 1, 2g of antioxidant 1010, 2.5g of diisophenyl peroxide, and 0.4g of polyethylene wax into a high-speed kneader, set the temperature to 110°C, knead for 45min, and then cool to room temperature to obtain an outer sheath mixture;
[0062] Step 2: Add the outer sheath mixture into a twin-screw extruder, set the temperature to 170° C., set the screw speed to 250 r / min, melt-extrude and granulate to obtain an outer sheath composite material.
[0063] Comparative Example 3
[0064] Preparation method of outer sheath composite material
[0065] Step 1, add 55g of metallocene linear low-density polyethylene, 15g of ethylene-vinyl acetate copolymer, 10g of high-density polyethylene, 5g of boehmite, 6g of the high-temperature resistant component prepared in Example 1, 2g of antioxidant 1010, 2.5g of diisophenyl peroxide, and 0.4g of polyethylene wax into a high-speed kneader, set the temperature to 110°C, knead for 45min, and then cool to room temperature to obtain an outer sheath mixture;
[0066] Step 2: Add the outer sheath mixture into a twin-screw extruder, set the temperature to 170° C., set the screw speed to 250 r / min, melt-extrude and granulate to obtain an outer sheath composite material.
[0067] Comparative Example 4
[0068] Preparation method of outer sheath composite material
[0069] Step 1: Add 55g of metallocene linear low-density polyethylene, 15g of ethylene-vinyl acetate copolymer, 10g of high-density polyethylene, 2g of antioxidant 1010, 2.5g of diisopropyl peroxide, and 0.4g of polyethylene wax into a high-speed kneader, set the temperature to 110°C, knead for 45 minutes, and then cool to room temperature to obtain an outer sheath mixture;
[0070] Step 2: Add the outer sheath mixture into a twin-screw extruder, set the temperature to 170° C., set the screw speed to 250 r / min, melt-extrude and granulate to obtain an outer sheath composite material.
[0071] Performance Testing
[0072] Performance test of the outer sheath composite materials prepared in Example 1 to Example 3 and Comparative Example 1 to Comparative Example 4:
[0073] The outer sheath composite materials prepared in Example 1 to Example 3 and Comparative Example 1 to Comparative Example 4 were prepared into samples that met the test standards. The tensile strength of the samples was tested according to the GB / T 1040.1-2018 standard; the bending strength of the samples was tested according to the GB / T 9341-2008 standard to determine the toughness of the samples; the Vicat softening temperature was tested according to the GB / T 1633-2000 standard to determine the high temperature resistance of the samples; the oxygen index of the samples was tested according to the GB / T 2406.2-2009 standard to determine the flame retardant properties of the samples; the specific test results are shown in the following table:
[0074]
[0075] It can be seen from the above table that the power cable outer sheath composite materials prepared in Examples 1 to 3 of the present invention have excellent tensile strength, toughness, high temperature resistance and flame retardancy. Among them, the test result of Example 2 is the best. Comparative Example 1 does not add the high temperature resistant component, and cannot utilize the crosslinking of the high temperature resistant component with the polyethylene matrix and the high rigidity and high temperature resistant structure of the benzimidazole in the high temperature resistant component to improve the high temperature resistance of the composite material, and cannot utilize the polybutadiene molecular chain and the crosslinking network formed with the polyethylene matrix to improve the toughness of the outer sheath composite material. Therefore, the Vicat softening temperature and flexural strength test results are poor; Comparative Example 2 does not add flame retardant additives, and cannot utilize boehmite modified with a nitrogen-phosphorus flame retardant system for synergistic flame retardancy, and cannot utilize the advantages of boehmite to enhance the mechanical properties of the outer sheath composite material, so the tensile strength and oxygen index test results are poor; Comparative Example 3 adds unmodified boehmite, which has a certain flame retardant effect, but is prone to agglomeration, which affects the mechanical properties of the outer sheath composite material, so the tensile performance and oxygen index test results are poor; Comparative Example 4 does not add flame retardant additives and high temperature resistant components, so the tensile strength, flexural strength, Vicat softening temperature and oxygen index test results are poor.
[0076] The outer sheath composite material prepared in Example 1 to Example 3 is used to manufacture a low-smoke, halogen-free, flame-retardant polyolefin power cable. The specific manufacturing method includes the following steps:
[0077] (i) Twisting copper wires to form a copper core, coating the outer surface of the copper core with a polyethylene insulation layer through an extrusion device, and sheathing the outer surface of the copper core coated with the insulation layer with a copper wire braided shielding layer to obtain a cable core;
[0078] (ii) The outer surface of the cable core is wrapped with a single-sided corrugated aluminum tape to form an inner protective layer, the outer surface of the inner protective layer is filled with alkali-free rock wool rope to form a filling layer, the outer surface of the filling layer is coated with an armor layer made of twisted steel wires, and the outer sheath composite material is extruded and coated on the surface of the armor layer to obtain a power cable.
[0079] The above contents are merely examples and explanations of the concept of the present invention. Those skilled in the art may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the concept of the invention or exceed the scope defined by the claims, they shall all fall within the protection scope of the present invention.
Claims
1. A low-smoke, halogen-free, flame-retardant polyolefin sheathed power cable, characterized in that: The manufacturing method of the power cable comprises the following steps: (1) Twisting copper wires to form a copper core, coating the outer surface of the copper core with a polyethylene insulation layer through an extrusion device, and sheathing the outer surface of the copper core coated with the insulation layer with a copper wire braided shielding layer to obtain a cable core; (2) Wrapping the outer surface of the cable core with a single-sided corrugated aluminum strip to form an inner protective layer, filling the inner protective layer with an alkali-free rock wool rope to form a filling layer, coating the outer surface of the filling layer with an armor layer made of twisted steel wires, and extruding and coating the outer sheath composite material on the surface of the armor layer to obtain a power cable; The outer sheath composite material comprises the following raw materials in parts by weight: 50-60 parts of metallocene linear low-density polyethylene, 10-20 parts of ethylene-vinyl acetate copolymer, 5-15 parts of high-density polyethylene, 3-6 parts of flame retardant additives, 4-8 parts of high-temperature resistant components, 1-3 parts of antioxidants, 1.5-3.5 parts of cross-linking agents, and 0.3-0.5 parts of lubricants; The method for preparing the flame retardant additive comprises the following steps: Step A, adding boehmite and glycine to deionized water, ultrasonically dispersing for 15-30 minutes, reflux reaction, centrifuging, washing, and drying at 55-65° C. for 6-8 hours to obtain modified boehmite; Step B, adding modified boehmite to tetrahydrofuran, ultrasonically dispersing for 10-15 minutes, adding diethyl allyl phosphate and triethylamine, stirring for 8-10 hours, filtering, washing, and drying to obtain a flame retardant additive; The preparation method of the high temperature resistant component is as follows: Add the carboxyl-terminated polybutadiene liquid rubber to N,N-dimethylformamide, stir and dissolve, then add 2-(4-aminophenyl)-5-aminobenzimidazole and a catalyst, react at room temperature for 8-12 hours, and obtain a high temperature resistant component after reduced pressure distillation and drying; The number average molecular weight of the carboxyl-terminated polybutadiene liquid rubber is 1000; The catalyst is 4-dimethylaminopyridine and N,N-dicyclohexylcarbodiimide.
2. The low-smoke, halogen-free, flame-retardant polyolefin sheathed power cable according to claim 1, characterized in that: The preparation method of the outer sheath composite material comprises the following steps: Step 1: Add metallocene linear low-density polyethylene, ethylene-vinyl acetate copolymer, high-density polyethylene, flame retardant additives, high-temperature resistant components, antioxidants, cross-linking agents, and lubricants into a high-speed kneading machine, set the temperature to 100-120°C, knead for 30-60 minutes, and then cool to room temperature to obtain an outer sheath mixture; Step 2: Add the outer sheath mixture into a twin-screw extruder, set the temperature to 160-180° C., set the screw speed to 150-300 r / min, melt-extrude and granulate to obtain an outer sheath composite material.
3. The low-smoke, halogen-free, flame-retardant polyolefin sheathed power cable according to claim 1, characterized in that: The antioxidant is antioxidant 1010 or antioxidant 1076; the cross-linking agent is diisopropyl peroxide or dibenzoyl peroxide; and the lubricant is any one of magnesium stearate, stearic acid and polyethylene wax.
4. The low-smoke, halogen-free, flame-retardant polyolefin sheathed power cable according to claim 1, characterized in that: In step A, the average particle size of the boehmite is 3.5 μm.
5. The low-smoke, halogen-free, flame-retardant polyolefin sheathed power cable according to claim 1, characterized in that: In step A, the reflux reaction time is 14-18h.
Citation Information
Patent Citations
Low-smoke halogen-free flame-retardant power cable
CN115322468A
Thermoplasticity polyimide compound with low modulus and high cementitiousness and application and preparation method thereof
CN107916090A
DAPBI modified waterborne polyurethane coating and preparation method thereof
CN109135530A
Cited By
Preparation method and application of flame-retardant medium-voltage power cable
CN122822494A
Low-smoke high-temperature-resistant polyolefin sheath high-voltage cable and preparation method thereof
CN122968042A